Multigene mutation analysis of metastatic lymph nodes in non-small cell lung cancer diagnosed by endobronchial ultrasound-guided transbronchial needle aspiration - Nakajima, Takahiro; Yasufuku, Kazuhiro; Nakagawara, Akira; Kimura, Hideki; Yoshino, Ichiro (Chest, 2011)
The importance of biomarker analysis in patients with non-small cell lung cancer (NSCLC) is well known. The purpose of this study was to analyze the mutation status of multiple genes in metastatic lymph nodes obtained by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and to examine the correlation between treatments and outcomes. Genetic alterations were analyzed in metastatic hilar or mediastinal lymph nodes diagnosed by EBUS-TBNA in 156 patients with NSCLC. Epidermal growth factor receptor (EGFR) was analyzed using the peptide nucleic acid-locked nucleic acid polymerase chain reaction clamp method (n = 156). V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (K-ras) (exons 2-3) and tumor protein 53 (p53) (exons 4-8) were analyzed by direct sequencing (n = 113). In addition, retrospective chart review was performed for clinical data analysis. EGFR gene mutations were detected in 42 cases (26.9%). Twenty-three patients with EGFR mutations received gefitinib, with an overall response rate (partial response [PR]) of 54.5% and disease control rate (PR + stable disease) of 86.4% (Response Evaluation Criteria in Solid Tumors). K-ras gene mutations were detected in four cases (3.5%), and p53 gene mutations were detected in 47 cases (41.6%). Fifty-two patients underwent conventional chemotherapy (46 patients underwent platinum-based chemotherapy). Patients with p53 gene mutations showed chemoresistance (progressive disease of 42.9%, P = .0339) and a relatively poor prognosis after chemotherapy (P = .1391). Multigene mutation analysis can be performed in EBUS-TBNA samples of metastatic lymph nodes from patients with NSCLC. EBUS-TBNA allows genetic evaluation of tumor cells within the metastatic node, which may allow physicians to better select treatments, particularly EGFR tyrosine kinase inhibitors.